Quantitative Trait Locus Mapping of Salt Tolerance and Identification of Salt-Tolerant Genes in Brassica napus L - Lang, Lina; Xu, Aixia; Ding, Juan; Zhang, Yan; Zhao, Na; Tian, Zhengshu; Liu, Yaping; Wang, Yang; Liu, Xia; Liang, Fenghao; Zhang, Bingbing; Qin, Mengfan; et al. (Frontiers in Plant Science, 2017)
Salinity stress is one of typical abiotic stresses that seriously limit crop production. In this study, a genetic linkage map based on 532 molecular markers covering 1341.1cM was constructed to identify the loci associated with salt tolerance in Brassica napus. Up to 45 quantitative trait loci (QTLs) for ten indicators were identified in the F2:3 populations. These QTLs can account for 4.80-51.14% of the phenotypic variation. A major QTL, qSPAD5 on LG5 associated with chlorophyll can be detected in three replicates. Two intron polymorphic (IP) markers in this QTL region were developed successfully to narrow down the QTL location to a region of 390kb. A salt tolerance related gene Bra003640 was primary identified as the candidate gene in this region. The full length of the candidate gene was 1063bp containing three exons and two introns in Brassica napus L. The open reading frame (ORF) is 867bp and encodes 287 amino acids. Three amino acid differences (34, 54, and 83) in the conserved domain (B-BOX) were identified. RT-qPCR analysis showed that the gene expression had significant difference between the two parents. The study laid great foundation for salt tolerance related gene mapping and cloning in B. napus L.